Aggregate consumption and debt accumulation: An empirical examination of US household behavior - KIM, Yun K. (Institutional Knowledge at Singapore Management University, 2015)
The outbreak of the financial crisis in 2008 witnessed a significant contraction in US consumption spending, as households began deleveraging following a period marked by historically high levels of household borrowing. These events call into question the canonical life-cycle theory of consumption, with its benign view of debt as a neutral instrument of optimal intertemporal expenditure smoothing. This paper draws attention to an alternative, post-Keynesian account of consumption spending in which current income, household borrowing and household indebtedness all affect current consumption. Central to the analysis is an empirical investigation of US consumption spending since the 1950s. The results of this inquiry cast doubt on the life-cycle hypothesis, but are congruent with the alternative, post-Keynesian account of consumption.